The synergy amongst factors influencing pre-service science teachers’ perceptions of inclusive education - Eric Appiah-Twumasi; Peter Atakorah Ofori; Benedict Osei-Owusu; Eric Twum Ampofo (Interdisciplinary Journal of Sociality Studies, 2024)
This study explores the synergy among factors influencing Ghanaian pre-service science teachers’ perceptions of inclusive education. The factors considered were desirable outcomes (DO) of inclusive education, implementation of inclusivity (IM), and willingness to adopt inclusivity (W). The study employed the explanatory sequential variant of the mixed-methods research design, using 503 pre-service science teachers from the Akenten Appiah-Menka University of Skills Training and Entrepreneurial Development. The instruments used were a five-point Likert scale questionnaire and a semi-structured interview guide. Quantitative data were analysed using path analysis through structural equation modelling (SEM) employing Analysis of Moment Structures (AMOS) version 23. Qualitative data from the interviews were, however, analysed using thematic analysis. Quantitative findings revealed that the implementation of inclusive education significantly predicted Ghanaian pre-service science teachers’ perceptions of inclusive education. However, willingness to adopt inclusivity and desirable outcomes of inclusive education were not significant contributors. Qualitative findings, however, revealed that practical application and hands-on experience, availability of resources and support, self-efficacy, classroom diversity and time constraints, and the need for further training might have explained the non-significant influence of desirable outcomes of inclusive education and willingness to adopt inclusivity on the perceptions of Ghanaian pre-service science teachers regarding inclusive education. It was therefore recommended, among other things, that teacher training institutions in Ghana should prioritise experiential learning opportunities, such as intensive inclusive teaching practicums, classroom simulations, and mentorship programmes, which can bridge the gap between theoretical instruction and practical application.